Theory and numerical modelling of parity-time symmetric structures in photonics: boundary integral equation for coupled microresonator structures - Phang, Sendy; Vukovic, Ana; Gradoni, Gabriele; Sewell, Phillip; Benson, Trevor M.; Creagh, Stephen C. (Springer Nature, 2017)
The spectral behaviour and the real-time operation of Parity-Time (PT) symmetric coupled resonators are investigated. A Boundary Integral Equation (BIE) model is developed to study these structures in the frequency domain. The impact of realistic gain/loss material properties on the operation of the PT-symmetric coupled resonators is also investigated using the time-domain Transmission-Line Modelling (TLM) method. The BIE method is also used to study the behaviour of an array of PT-microresonator photonic molecules.